(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study was taken as an effort to assess the effects of paeonol on diabetic cardiomyopathy. Diabetes was induced in separate groups of Sprague-Dawley rats using streptozotocin. Treatment group animals received paeonol (50, 100 or 200 mg/kg body weight/day; orally) 5 weeks after streptozotocin induction for 6 weeks. Paeonol strikingly reduced myocardial apoptosis and improved cardiac function and myocardial architecture. Serum levels of glucose, reactive oxygen species and inflammatory mediators (TNF-α, IL-6 and IL-1β) were significantly reduced with decreased accumulation of collagen in the cardiac tissue. Paeonol modulated p-Akt, glycogen synthase kinase-3β and glycogen synthase, while significantly down-regulated protease-activated receptor-1, caspase-3, TNF-α, NF-κB p65, and p-Iκ-Bα expressions. Paeonol effectively suppressed diabetic cardiomyopathy by improving myocardial function, regulating the inflammatory responses and Akt signalling.